Post Partum Haemorrhage : A Review of Prevention And Management - Sri Handayani (Jurnal Keperawatan GSH, 2021)
One of leading causes of severe maternal morbidity and mortality worldwide is postpartum haemorrhage. It is defined as a blood loss of 500 ml or more within 24 hour after birth. The most common cause of postpartum haemorrhage is uterine atony, the second cause is retained placenta, the other etiology are the lower segment as an implantation site, placenta previa, placenta accreta, coagulopathy and genital tract trauma. In this review, we describe the current state of the literature as it applies to postpartum haemorrhage, focusing on prevention and management aspects, as well as relevant obstetric consideration necessary to treat this challenging problem. Postpartum haemorrhage after birth is preventable through use of prophylactic uterotonics during the third stage of labor with timely and appropriate care and management. Active management of the third stage of labor is a well-established protocol that has been shown to significantly reduce the incidence of postpartum hemorrhage. Skill of birth attendance and adequate caregivers training have important roles in increasing maternal safety. For safer motherhood, a holistic approach are needed.